Peace diplomacy, global justice and international agency : rethinking human security and ethics in the spirit of Dag Hammarskjöld / edited by Carsten Stahn and Henning Melber. - Stahn, Carsten, 1971-; Melber, Henning (Cambridge University Press, 2014)
As UN Secretary-General, Dag Hammarskjöld shaped many of the fundamental principles and practices of international organisations, such as preventive diplomacy, the ethics of international civil service, impartiality and neutrality. He was also at the heart of the constitutional foundations and principles of the UN. This tribute and critical review of Hammarskjöld's values and legacy examines his approach towards international civil service, agency and value-based leadership, investigates his vision of internationalism and explores his achievements and failures as Secretary-General. It draws on specific conflict situations and strategies such as Suez and the Congo for lessons that can benefit contemporary conflict resolution and modern concepts such as human security and R2P. It also reflects on ways in which actors such as international courts, tribunals and the EU can benefit from Hammarskjöld's principles and experiences in the fields of peace and security and international justice.